IMPACT ONLINE LEARNING POLICY DROPS SEMESTER GRADES OF STUDENTS OF FISIP IN CENDERAWASIH UNIVERSITY YEAR 2020-2021 - Ferinandus Leonardo Snanfi (Sosiohumaniora, 2022)
This study aims to investigate the impact online learning policy, issued Ministry of Education and Culture Republic of Indonesia, followed Rector of Cendrawasih University and Dean of Faculty of Social and Political Sciences. Policy impact drops semester grades students from seven program studies in Faculty of Social and Political Sciences: Governance Science, Public Administration, Business Administration, International Relations, Anthropology, Welfare, and Library. To analyze problem, Merilee S. Grindle’s policy theory was used. Qualitative research method. The study was conducted in Faculty of Social and Political Sciences of Cenderawasih University year 2020-2021. Study involves 20 respondents: 8 are lecturers of Faculty of Social and Political Sciences and 12 are students of Faculty of Social and Political Sciences. Qualitative analyzed method was used; data collection methods interview, observation, documentation have been analyzed according to the reality. The result shows that the second semester grades of students of batch 2021 drastically drop due to internet trouble, unavailable facilities, infrastructures, and server building for Wi-Fi in Faculty of Social and Political Sciences, Cenderawasih University, districts in Papua Province, and districts in West Papua Province. Recommendation for Dean of Faculty of Social and Political Sciences of Cenderawasih University, Rector of Cenderawasih University, Ministry of Education and Culture Republic of Indonesia is to allow face to face learning with number of students grouped into several daily shifts and good implementation of covid-19 health protocols in Faculty of Social and Political Sciences of Cenderawasih University.